Upaya Preventif Kejaksaan Dalam Pembangunan Desa di Wilayah Pemerintah Kabupaten Gunungkidul - Nanang Dwi Setiyoaji; Fransisca Romana Harjiyanti; Hartanti Hartanti (Universitas Janabadra, 2019)
Village funds are a central government tool for village development, village development is one of the national development agendas. The problem that then arises is that relatively new regulations have not been fully understood by village government implementers. Another thing that is quite a concern is that the greater the amount of funds disbursed by the central government to the villages. The potential for fraudulent management of village funds needs to be anticipated through efforts by the District Prosecutor's Office of Gunungkidul District. The problems of this research are: 1 How is the Prosecutive Efforts of Prosecutors in Rural Development in the Gunungkidul District Government Area? 2 What obstacles do the Gunungkidul District Prosecutors' Guards and Regional Guard face? Based on the results of the research and discussion it can be concluded: 1 Lack of coordination of the Regional Government with the Prosecutor's Office, especially in terms of mentoring and legal information by the Gunungkidul District Prosecutor's Office. So that the assistance offered by the Prosecutor's Office is not an interesting thing to do. 2 Passive Communities that tend to be Apathetic when the Attorney Office conducts Legal Counseling. They assume that applying for legal assistance to the Prosecutor's Office will make it difficult for them to carry out development using Village funds.Suggestions: 1 For the government to review the Village funds budget to be right on target and in accordance with the objectives of this purpose by appointing a Team according to the capabilities of their respective fields so that the development process is not constrained. In addition, in terms of assistance and supervision of the government.